2022
DOI: 10.1186/s44158-022-00048-5
|View full text |Cite
|
Sign up to set email alerts
|

High rates of impaired quality of life and social and economic problems at 6 months after COVID-19-related ARDS

Abstract: Purpose Assess long-term quality of life (HR-QoL) and socio-economic impact in COVID-19-related ARDS (C-ARDS) survivors. Methods C-ARDS survivors were followed up at 6 months in this prospective, cohort study. HR-QoL was assessed using SF-36 and EQ-5D-5L, and the socio-economic burden of COVID-19 was evaluated with a dedicated questionnaire. Clinical data were prospectively recorded. Results Seventy-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The outbreak caused by SARS‐CoV‐2 threatened the world with increasing infection and massive casualties. 1 , 2 During the pandemic, the SARS‐CoV‐2 subvariants evolved rapidly with enhanced transmissibility and the alarmingly rising rate of infection. The constantly mutated S protein under high‐pressure selection rendered vaccines and antibodies somewhat less effective.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The outbreak caused by SARS‐CoV‐2 threatened the world with increasing infection and massive casualties. 1 , 2 During the pandemic, the SARS‐CoV‐2 subvariants evolved rapidly with enhanced transmissibility and the alarmingly rising rate of infection. The constantly mutated S protein under high‐pressure selection rendered vaccines and antibodies somewhat less effective.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) caused an outbreak that started around December 2019 and quickly spread. 1 The outbreak caused a global threat to human physical and mental health worldwide. 2 According to Centers for Disease Control and Prevention, the effects of coronavirus disease 2019 (COVID‐19) may be long lasting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the structured telephone interview, patients were administered a set of questionnaires including: the five-level, five-dimensional EuroQoL questionnaire (EQ-5D-5L) [ 28 ], the EuroQol Visual Analog Scale (EQ VAS) Short Form, and the Short-Form Health Survey 36Version 2 (SF-36v2) [ 29 ] to assess the HR-QoL; a question set designed to investigate the socioeconomic status and changes in family and work circumstances and care needs [ 12 ]; the Italian version of the Impact of Event Scale—Revised (IES-R) to assess PTSD [ 30 ]. Telephone interviews lasted an average of 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported a substantial increase in mental health challenges among survivors [ 5 , 6 , 7 ], but also in caregivers [ 3 ] and frontline healthcare workers [ 8 , 9 ], exposing public health to great challenges [ 10 ]. Mental health problems after intensive care unit (ICU) discharge during the COVID-19 pandemic are particularly numerous and disabling [ 11 , 12 ], possibly as a consequence of exposure to extremely stressful acute events and particularly severe forms of disease, besides the often very long hospital stay and the incidence of post-intensive-care syndrome [ 6 , 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%